A Rare Case of Extrauterine Endometrial Stromal Sarcoma Arising from Deep Pelvic Endometriosis: Role of Multidisciplinary Team Meeting - Long, Xueying; Pei, Yigang; Masokano, Ismail B.; Zhu, Xin; Lin, Wei; He, Siting; Liu, Hui (Current Medical Imaging, 2023)
Introduction: Extrauterine endometrial stromal sarcoma (EESS) arising from Deep pelvic endometriosis (DPE) has a poor life quality and is difficult to diagnose pre-operatively. However, the patient’s quality of life can be improved when it is diagnosed precisely and managed successfully. Case Report: A 35-year-old woman presented to our hospital with a 3-month history of hematochezia and anal pain. Initially, she was misdiagnosed as a rectal stromal tumor and then precisely diagnosed as having EESS from DPE following several multidisciplinary team (MDT) meetings. The lesion was shrunk by gonadotrophin-releasing hormone agonist (GnRH-α) treatment and then resected with minimal trauma. Conclusion: MDT is crucial in the treatment of the patient. It can promote individualized treatment and improve patient’s quality of life.
Keywords: Treatment